2012
DOI: 10.1186/ar3827
|View full text |Cite
|
Sign up to set email alerts
|

Levels of adiponectin, a marker for PPAR-gamma activity, correlate with skin fibrosis in systemic sclerosis: potential utility as a biomarker?

Abstract: IntroductionProgressive fibrosis in systemic sclerosis (SSc) is linked to aberrant transforming growth factor beta (TGF-beta) signaling. Peroxisome proliferator-activated receptor gamma (PPAR-gamma) blocks fibrogenic TGF-beta responses in vitro and in vivo. Reduced expression and function of PPAR-gamma in patients with SSc may contribute to progression of fibrosis. Here we evaluated the levels of adiponectin, a sensitive and specific index of PPAR-gamma activity, as a potential fibrogenic biomarker in SSc.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 26 publications
9
89
0
1
Order By: Relevance
“…Masui et al [12], Winsz-Szczotka et al [13] and Ozgen et al [14] have showed that serum/plasma adiponectin levels in SSc patients were significantly lower than that in normal subjects, while Lakota et al [15] and Arakawa et al [16] have showed serum/plasma adiponectin levels of SSc patients were similar to that in healthy subjects. For the circulating leptin levels in SSc patients, the inconclusive or contradictory results have also been observed.…”
Section: Introductionmentioning
confidence: 82%
“…Masui et al [12], Winsz-Szczotka et al [13] and Ozgen et al [14] have showed that serum/plasma adiponectin levels in SSc patients were significantly lower than that in normal subjects, while Lakota et al [15] and Arakawa et al [16] have showed serum/plasma adiponectin levels of SSc patients were similar to that in healthy subjects. For the circulating leptin levels in SSc patients, the inconclusive or contradictory results have also been observed.…”
Section: Introductionmentioning
confidence: 82%
“…Treatment of fibroblasts with adiponectin, an adipocyte-derived peptide that is reduced in patients with SSc, blocked TLR-dependent fibrotic responses. 58,59 Remarkably, adiponectin induces sustained upregulation of A20 in fibroblasts. Pharmacologic agents that induce A20 expression, such as vitamin E (c-tocotrienol) and adiponectin, hold promise as antifibrotic therapies by restoring endogenous A20 expression, particularly when targeted in a tissue-restricted manner, such as by topical application.…”
Section: Multiple Mechanisms To Prevent Aberrant Tlr4 Activationmentioning
confidence: 99%
“…PPARγ binds directly to a functional PPAR-responsive element (PPRE) in adiponectin promoter, leading to enhancement of adiponectin gene transcription [17]. Indeed, adiponectin was believed to be a marker for activity of PPARγ [18].…”
Section: H O S T E D Bymentioning
confidence: 99%